Bactericidal effect on skin mucosa of dietary guava (Psidium guajava L.) leaves in hybrid tilapia (Oreochromis niloticus × O. mossambicus). (15th September 2020) - Ceballos-Francisco, Diana; Castillo, Yussaira; De La Rosa, Francisco; Vásquez, William; Reyes-Santiago, Raysa; Cuello, Andreina; Cuesta, Alberto; Esteban, María Ángeles
Abstract: Ethnopharmacological relevance: Due to the intensification practices in global aquaculture, fish are often confined in small volumes, which can results in outbreak diseases. In this context, the use of antibiotics is very usual. Thus, looking for natural substance able to reduce the use of the antibiotics is imperative. Among them, there is a great interest at present in the study of medicinal plants such as guava ( Psidium guajava L.). These plants could help to develop a more sustainable aquaculture all over the world. The application of guava in traditional medicine dates for centuries and it is widely used in tropical countries for the treatment of diseases in human and animals. Aim of the study: The purpose of this work was to study the effects of the dietary administration of dried leaves of Psidium guajava on the skin mucosal immunity of hybrid tilapia ( Oreochromis niloticus × O. mossambicus ). Furthermore, the ability of this plant to inhibit the bacterial load in different tissues after an experimental infection with Vibrio harveyi was studied . Materials and methods: P. guajava leaves collection and the experimentation was carried out in Dominican Republic. Fish were fed with a commercial diet supplemented with guava leaf at different concentrations (0%, 1.5% and 3%) for 21 days before being intraperitoneally injected with V. harveyi (1 × 10 4  cells mL −1 ). Thereafter, several immune activities were measured in fish skin mucus and after 48 h of injection, the skin, spleen and liver were collected to analyse the bactericidal activity of guava leaf and the gene expression of some immune related genes. Results: The administration of P. guajava leaves significantly modulated some immune-related enzymes (protease, antiprotease and peroxidase) in the skin mucus of hybrid tilapia. In addition, the bacterial load after V. harveyi infection in skin, spleen and liver significantly reduced in fish supplemented with guava leaves. Finally, the expression profile of hepcidin gene in skin and liver was modulated in fish feed with control diet after V. harveyi infection. Conclusion: These results demonstrate that the dietary intake of guava leaves increases the skin mucosal barrier defences of hybrid tilapia and confers protection against V. harveyi colonization. Graphical abstract: Image 1 Highlights: Dietary supplementation with guava leaf strengthens skin mucosal immunity in hybrid tilapia. Skin, spleen and liver are the target organs for Vibrio harveyi in hybrid tilapia. Dietary supplementation with guava leaf at 1.5% and 3% reduces considerably the bacterial load in hybrid tilapia. Guava leaf may be anappropriate substitute to antibiotics in aquaculture systems.